Food Policy Options : Preventing and Controlling Nutrition Related Non-Communicable Diseases - World Health Organization; World Bank (World Bank, Washington, DC, 2013)
Although diet structure and activity throughout the developing world have shifted drastically over the past several decades, little is known about effective policies to influence the supply and demand for food to control the undesirable effects, such as obesity, heart disease and cancer, of those shifts. Two questions specifically need to be addressed: a) Are the traditional policy levers for crops and livestock still important and feasible options, considering the latest developments in processing, distribution and marketing? b) What research should be done in the process of formulating an 'Action Agenda' over the longer term. The answer to question one, concerns 'Traditional' versus 'New Policy Levers', and includes: i) recognition of the limitations of conventional food policies; ii) demanding truth in advertising; iii) harnessing the influence of supermarkets and multinational corporations; iv) choosing realistic options to shift demand; v) addressing internal infrastructure; vi) using schools for targeted intervention. Currently, few studies allow linkage of prices, diet, and health outcomes in any systematic manner that considers the timing of the changes.